2016
DOI: 10.1002/14651858.cd011020.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Technological aids for the rehabilitation of memory and executive functioning in children and adolescents with acquired brain injury

Abstract: This review provides low-quality evidence for the use of technology-based interventions in the rehabilitation of executive functions and memory for children and adolescents with TBI. As all of the included studies contained relatively small numbers of participants (12 to 120), our findings should be interpreted with caution. The involvement of a clinician or therapist, rather than use of the technology, may have led to the success of these interventions. Future research should seek to replicate these findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 58 publications
0
37
0
2
Order By: Relevance
“…Prospective memory impairment is one of the most common sequelae of brain injury and can have a debilitating effect on the lives of young people with brain injury [1][2][3][4][5][6][7][8][9]. Research has suggested that using smartphones as compensatory aids can help to improve functioning in children and adolescents [1,18,20].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prospective memory impairment is one of the most common sequelae of brain injury and can have a debilitating effect on the lives of young people with brain injury [1][2][3][4][5][6][7][8][9]. Research has suggested that using smartphones as compensatory aids can help to improve functioning in children and adolescents [1,18,20].…”
Section: Resultsmentioning
confidence: 99%
“…Memory impairment can interfere with learning and access to education, everyday adaptive functioning and social participation [5][6][7][8][9]. Thus, interventions targeted at improving prospective memory are often employed in cognitive rehabilitation, via remedial or compensatory strategies [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations